DIRECTIONS OF IMPROVING THE LEVEL OF ENTERPRISES COMPETITIVENESS IN THE MACHINE-BUILDING INDUSTRY OF UKRAINE - YEPIFANOVA, IRYNA; DZHEDZHULA, VIACHESLAV; BALZAN, MARINA; HUMENIUK, VIKTORIYA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article determines and systematizes the existing obstacles to the development of competitiveness of enterprises in the machine-building industry of Ukraine. One of the most important problems facing the domestic economy is to ensure stable economic growth not only in the raw materials industries, but above all, in the leading industries of the industrial complex, whose center of gravity is the machine-building industry. Machine-building complex - one of the leading in the industry of Ukraine, which integrates a system of research, design and technological organizations; It is engineering determines the socio-economic and technological and technological level of state development, the competitiveness of its productions. Effective functioning and maintenance of a high level of competitiveness, is important for modern Ukrainian machine-building enterprises.The article investigates  the main constraints of competitiveness of enterprises of the machine-building industry of Ukraine, which related to change, connections and competition. The development of mechanical engineering under the influence of various factors is not predictable, not by plans and programs, which are formed by governments taking into, account the needs of industrial products and the requirements of globalization of the world economy. It is accompanied by accumulation of problems that adversely affect the development and general condition of machine-building corporations. The situation is worsening with a decrease in the time span between global crises, which adversely affect the state of the national economy of Ukraine and the types of economic activity. Despite the negative trends that are observed in industry and in machine building, there is a possible directions of solving the existing obstacles and restrictions.
Keywords: machine-building industry of Ukraine; competitiveness; competition; restraining factors; constraint